FORECAST AGRICULTURAL CROP YIELDS USING DYNAMIC SERIES - Ishniyazov Baxrom Normamatovich (Web of Journals Publishing, 2024)
In this article, when teaching students the topic of predicting yields using dynamic series of mathematics, the support of theoretical data directly on the solution of Agricultural Issues is studied using pedagogical experiments, which leads students to better master science, strengthen their professional training.
Keywords: experiment, soil fertility, yield, random factors, timed(dynamic) series, statistical analysis, statistical hypotheses, random process, trend, autocorrelation coefficient, interval statistical assessment, linear linkage, least squares method, correlation linkage.